2020
DOI: 10.1007/s43032-020-00221-7
|View full text |Cite
|
Sign up to set email alerts
|

Curbing Obesity from One Generation to Another: the Effects of Bariatric Surgery on the In Utero Environment and Beyond

Abstract: Approximately 250,000 individuals seek bariatric surgery each year in the U.S. for the long-term resolution of obesity-related comorbidities. Greater than 80% of these individuals are women and approximately half are of child-bearing age. Although there are many positive metabolic benefits that are realized through surgical weight loss for both men and women, the various long-term hormonal, molecular, nutrient and epigenetic changes following bariatric surgery have not been evaluated for the surgical recipient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 142 publications
(211 reference statements)
0
7
0
Order By: Relevance
“…The implications of these findings for women open up a wealth of opportunities to explore novel, central nervous system–targeted approaches to treating sexual dysfunction in women. In an analogous fashion, the lack of effective weight management for captive NHPs [ 205 , 206 ] and women [ 207 ] has led to successive gains in body weight over recent decades among immature and adult female NHPs and humans alike. The findings presented in this female NHP study suggests that future treatments designed to deliver bioactive estradiol to only the central nervous system, including the hypothalamus [ 119 ], may have potential to alleviate both sexual and metabolic dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…The implications of these findings for women open up a wealth of opportunities to explore novel, central nervous system–targeted approaches to treating sexual dysfunction in women. In an analogous fashion, the lack of effective weight management for captive NHPs [ 205 , 206 ] and women [ 207 ] has led to successive gains in body weight over recent decades among immature and adult female NHPs and humans alike. The findings presented in this female NHP study suggests that future treatments designed to deliver bioactive estradiol to only the central nervous system, including the hypothalamus [ 119 ], may have potential to alleviate both sexual and metabolic dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Mothers have a close interaction with offspring during pregnancy and early life. Research in humans and mice has made us aware that maternal obesity is directly related to poor offspring health [ 38 ], not only as a consequence of obesity-triggered pregnancy complications [ 39 ], but also as a result of epigenetic changes that are stable throughout generations. Indeed, several studies have shown that maternal obesity or increased fat intake induce transcriptional reprogramming [ 40 ], histone modifications [ 41 , 42 ], and DNA methylation changes in offspring [ 43 , 44 , 45 , 46 ].…”
Section: Maternal Obesity Affects Offspring Healthmentioning
confidence: 99%
“…In addition to common lifestyle interventions, the more severe forms of obesity are now treated by bariatric surgery, which is becoming increasingly common. Reported evidence based on studies of humans suggests that bariatric surgery is associated with both positive and negative pregnancy and neonatal outcomes [ 39 , 175 , 176 ]. These findings have been corroborated by studies in diet-induced obesity rats, where ventral sleeve gastrectomy has led to worsened pregnancies and offspring health [ 177 , 178 , 179 ].…”
Section: Reversibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Obese women need higher doses of gonadotropins for ovulation induction during IVF procedures (17). Obesity has an impact on gestation by increasing comorbidities associated with pregnancy: gestational diabetes mellitus, gestational hypertension, eclampsia, increased risk for maternal or fetal death, preterm delivery, intrauterine growth restriction and need for cesarian section (18).…”
Section: Reproductivementioning
confidence: 99%